Strengthening the policy, implementation, and accountability environment for quality care: experiences from quality of care network countries - Maliqi, Blerta; Cocoman, Olive; Dohlsten, Martin; Dussey, Selina; Hinton, Rachael; Mannah, Margaret T.; Muzigaba, Moise; Rammal, Tala; Sabiiti, Jesca; Yaqub, Nuhu; Banerjee, Anshu (Frontiers in Health Services, 2024)
Despite global commitment to universal health coverage with quality, poor quality of care (QOC) continues to impact health outcomes for mothers and newborns, especially in low-and-middle income countries. Although there is much experience from small-scale projects, without a long-term perspective it is unclear how to implement quality of care effectively and consistently for impact. In 2017, ten countries together with the WHO and a coalition of partners established the Network for Improving Quality of Care for Maternal, Newborn and Child Health (the Network). The Network agreed to pursue four strategic objectives—Leadership, Action, Learning and Accountability (LALA) for QOC. This paper describes, analyses and reflects on what has worked and some of the challenges faced in implementation of the LALA framework. The implementation of the LALA framework has served as a catalyst to develop an enabling environment for QOC in the Network countries through strengthening the policy, implementation, accountability and community engagement for quality care. Developing an enabling health system environment takes time, but it is possible and shows results. The implementation shows that health systems continue to face persistent challenges such as capacities to quickly scale up changes across subnational levels, limited workforce capability to implement quality improvement consistently and gaps in quality of relevant data. The implementation has also highlighted the need to develop new mechanisms for community engagement and learning systems that inform scaling up of good QOC practices across programmes and levels of care. Moving forward, the Network countries will build on the experiences and lessons learned and continue to strengthen the implementation of LALA strategic objectives for impact. We hope the Network experience will encourage other countries and partners to adopt the Network implementation model to enable delivery of quality care for everyone, everywhere, and actively collaborate and contribute to the QOC global learning network.